Atomic-Level Dynamics in Chemical Reactions: A Time-Resolved Spectroscopic Approach - Khaqan Ali Khan; Muhammad Irfan Jamil; Haji Muhammad; Zohaib Ahmad; Imran Hussain (Indus Journal of Social Sciences, 2025)
In recent decades, there have been incredible advances in time-resolved spectroscopic techniques, allowing further comprehension of ultrafast chemical reaction dynamics. Time-resolved high-harmonic spectroscopy (TR-HHS) and Coulomb explosion imaging have provided the unique opportunity to measure fast processes such as ring-opening reactions and conical intersection pathways with exquisite temporal resolution. For instance, TR-HHS has been used to explore the photochemical ring-opening reaction of 1,3-cyclohexadiene to 1,3,5-hexatriene, whereby the electronically excited state interconverts to vibrationally excited ground state within 80 femtoseconds before isomerization occurs approximately 400 femtoseconds after excitation. Similarly, Coulomb explosion imaging has been directly used to show ultrafast ring-opening in furan (gas phase) upon 198 nm excitation, occurring within 100 femtoseconds. Non-adiabatic excited-state dynamics in trans-1,3-butadiene have been established using time-resolved X-ray absorption spectroscopy and the importance of conical intersections in defining branching pathways for reactive processes has been confirmed. Time-resolved infrared and Raman spectroscopy are suitable for the real-time monitoring of vibrational marker modes, thereby providing information concerning some aspects of structural dynamics, for instance, those occurring during intramolecular hydrogen transfer or cleavage in organometallic compounds. There are just several steps to take before reaching the Zenith, and time will tell. The experiment is currently ongoing. These methodologies contribute to the understanding of fundamental chemical processes, providing an impetus for the development of photoactive materials and light-mediated biological applications. Constant advancements in the time-resolved spectroscopic methods would help to highlight even more the complexities of chemical dynamics, which would facilitate progress in many domains of science.